An investigation of the specificity and vividness of autobiographical memories and future events produced in response to disgust-related cues among individuals with eating disorders - Sevgi Bektas; Rowan Haslam; Shannon Hilton; Hubertus Himmerich; Valentina Cardi; Janet Treasure; Johanna Louise Keeler (Journal of Eating Disorders, 2025)
Abstract Background A deficiency in autobiographical memory functioning could be of relevance to the maintenance of an eating disorder (ED). Past research has found that people with EDs have difficulties in recalling specific details of autobiographical memories (AM) and in imagining future events. Our aim was to investigate AM and episodic future thinking (EFT) in individuals with anorexia nervosa (AN), binge-type eating disorders (Bulimia Nervosa or Binge Eating Disorders; BN/BED), and healthy controls (HCs) using negative cue words relevant to the experience of being disgusted and morally violated. Methods Remotely administered computerised versions of the autobiographical memory task (AMT) and the EFT task were used to measure the specificity and vividness of AMs and EFTs. Neutral or negative/moral disgust-relevant cues were used to elicit AMs and EFTs. The relationship between AM specificity and EFT specificity was explored. The predictor role of individual differences in childhood teasing and betrayal sensitivity on the specificity and vividness of AMT and EFTs induced by moral disgust-relevant cues was examined. Results Individuals with AN and BN/BED did not have difficulties retrieving specific and vivid details of AMs and imagining future events in both cue conditions. AM specificity predicted EFT specificity in AN and HC groups. Future events primed by neutral cues were rated as more vivid by the control group compared to those induced by negative cues. Participants with EDs who had greater levels of childhood teasing and betrayal sensitivity generated more vivid AMs and EFTs in response to moral disgust-related cues, which was not observed in HCs. Conclusions This study did not detect alterations in AMT and EFT characteristics in people with AN or binge-type EDs compared with HCs. The findings were discussed regarding sample characteristics (e.g., illness severity, ethnicity) and methodology (e.g., cue words) in the present study. Individual differences in childhood teasing and betrayal sensitivity may be related to more vivid negative memories and future events, which might increase the salience of past and future victimisation-related events.